Blood brain barrier: An overview on strategies in drug delivery, realistic in vitro modeling and in vivo live tracking. Issue 1 (2nd January 2016) - Pandey, Pawan Kumar; Sharma, Ashok Kumar; Gupta, Umesh
Abstract : Blood brain barrier (BBB) is a group of astrocytes, neurons and endothelial cells, which makes restricted passage of various biological or chemical entities to the brain tissue. It gives protection to brain at one hand, but at the other hand it has very selective permeability for bio-actives and other foreign materials and is one of the major challenges for the drug delivery. Nanocarriers are promising to cross BBB utilizing alternative route of administration such as intranasal and intra-carotid drug delivery which bypasses BBB. In future more optimized drug delivery system can be achieved by compiling the best routes with the best carriers. Single photon emission tomography (SPECT) and different brain-on-a-chip in vitro models are being very reliable to study live in vivo tracking of BBB and its pathophysiology, respectively. In the current review we have tried to exploit mechanistically all these to understand and manage the various BBB disruptions in diseased condition along with crossing the hurdles occurring in drug or gene delivery across BBB.